Development and competitiveness of Indonesian coffee exports: Case Studies: Georgia, Germany, Japan, Malaysia, Italy, Algeria, England, Belgium, India, Egypt for the period 2013-2022 - Indrawaty Sitepu; Medi Lilis Wenny Br. Nainggolan (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to determine the development and competitiveness of Indonesian coffee exports to Georgia, Germany, Japan, Malaysia, Italy, Algeria, England, Belgium, India, Egypt for the period 2013-2022. The data used is secondary data sourced from BPS, the Directorate General of Plantations and UN Comtrade. The data analysis methods used are description analysis, RAC (Revealed Comparative Advantage) and EPD (Export Product Dynamics). The results of the research show that: 1. The development of Indonesian coffee exports for the last ten years 2013-2022 has generally fluctuated, while to Georgia the last three years have increased consecutively and India for the last four years has increased consecutively. 2. The competitiveness of Indonesian coffee exports for the last ten years 2013-2022 using RCA (Revealed Comparative Advantage) analysis is strong for two countries, namely Georgia and Algeria, while for eight other countries, namely Germany, Japan, Malaysia, Italy, England, Belgium, India and Egypt is weak. With EPD (Export Product Dynamics) analysis, there are eight Raising Star countries, namely Germany, Japan, Malaysia, Algeria, England, Belgium, India and Egypt, while two lost opportunity countries are Georgia and Italy. Keywords: Competitiveness, Coffee exports, Development of Indonesian coffee exports